Determinants of tetanus immunization among pregnant women where tetanus has not been eliminated: a multilevel analysis of 6 countries - Werkneh Melkie Tilahun; Habtamu Geremew; Lamrot Yohannes Abay; Adugnaw Bantie Kebie; Mulat Belay Simegn (Frontiers in Global Women's Health)
BackgroundTwo or more doses of the tetanus toxoid (TT) vaccine in pregnancy afford the fetus passive immunity and reduce neonatal mortality by 96%. In developing nations, the use of TT during pregnancy is still uncommon but presents a serious risk to public health. Thus, the current study aimed to identify determinants of adequate TT immunization among pregnant women in six countries that have not eliminated maternal and neonatal tetanus.MethodsA cross-sectional study was conducted using recent demographic and health survey datasets from 6 countries that didn't achieve maternal and neonatal tetanus elimination. A total of 84,248 weighted samples were included. A multilevel logistic regression model was fitted. An adjusted odds ratio with a 95% CI and p-value < 0.05 was used to declare significant factors.ResultsBeing married [AOR = 1.36, CI: 1.20, 1.54], poorest [AOR = 1.46, CI: 1.36, 1.57], the poorer [AOR = 1.48, CI: 1.39, 1,59], middle [AOR = 1.33, CI: 1.26, 1.42], and the richer [AOR = 1.19, CI: 1.13, 1.26] wealth quintile, giving birth between the ages of 24 and 30 years [AOR = 1.10, CI: 1.04, 1.16], being primiparous [AOR = 1.09; CI: 1.02, 1.17], female house head [AOR = 1.13; CI: 1.06, 1.20], 4 and above antenatal care (ANC) visits [AOR = 5.94, CI: 5.60, 6.30], attending post-natal checkup [AOR = 1.18, CI: 1.13, 1.23], and institutional delivery [AOR = 1.22, CI: 1.18, 1.27] were positively related to adequate TT immunization. While unemployment [AOR = 0.68, CI: 0.66, 0.71], poor health facility visits [AOR = 0.72, CI: 0.70, 0.75], abortion [AOR = 0.89, CI: 0.85, 0.93], low community media exposure [AOR = 0.74, CI: 0.67, 0.81], and rural residence [AOR = 0.80, CI: 0.77, 0.84] were significant risk factors for inadequate TT immunization.ConclusionMarital status, wealth index, age at first birth, decision about women's health care, parity, sex of household head, ANC, postnatal checkup, distance to health facility, and health insurance were significant predictors of adequate TT vaccination. Therefore, TT immunization can be improved by promoting maternal employment, improving post-abortion care, media coverage, community literacy, and health accessibility, and encouraging pregnant women to receive ANC and postnatal care.